Effect of etchant containing an Urushiol monomer from lacquer sap on dentin biostability and bonding performance - Zhao, Ying; Xu, Xuanwen; Li, Lu; Zheng, Kai; Wang, Xiaoqian; Zhang, Ming; Xu, Yan (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: This study aimed to evaluate the effectiveness of urushiol as an additive to surface acid etchant on dentin structure, by assessing the biostability of dentin, and determine the bonding strengths of dentin and enamel to the composite in the complicated oral microecology. Methods: Etchants with different concentrations of urushiol (0.5, 1, or 3 wt%) were formulated and tested for their bonding performance. Demineralized dentin beams that were etched with experimental etchants were incubated in simulated body fluid solutions by evaluating the weight decrement after 1 month. The effects of urushiol on dentin and matrix metalloproteinases were confirmed by scanning electron microscopy (SEM). Moreover, the antibiotic actions of urushiol on the common cariogenic bacteria Streptococcus mutans, Streptococcus sanguinis, and Streptococcus gordonii as well as the biofilm were evaluated, and its effect on bacterial morphology was observed by scanning electron microscopy. Finally, enamel and dentin specimens were prepared from human molars to determine the depth of demineralization by the etchants and the relationship with the resin bond strengths to enamel and dentin (μTBS) and the morphology of the bonding interface. Results: Urushiol could interact with dentine and inhibit collagenase activity, resulting in biostable dentine. The application of the etchants containing 0.5, 1, or 3 wt% urushiol significantly improved the durability of the dentin bonding interface with its instinctive antibacterial property (p < 0.05). Conclusion: Urushiol not only improves dentin stability by interacting with collagen and inactivating MMP activity but also plays a role in the antibacterial effects in the complicated oral microecology. The effectiveness of urushiol etchant prolongs the longevity of bonded dental restorations without compromising clinical operation time.